DESIGN AND SIMULATION OF AIR CONDITIONING SYSTEM WITH HYDRONIC RADIANT PANELS IN FTMD ITB COWORKING SPACE - Mandiri, Mande
Energy consumption of air conditioning system can be the largest in a building. Energy efficient air conditioning methods are already studied and developed, but its application in Indonesia is not yet common. One of the methods that are already commonly used in other countries is hydronic radiant panels. Based on that background, this final project tries to apply hydronic radiant panels to FTMD ITB Coworking Space. The main literature used on this project to design the radiant panels are ASHRAE HVAC Systems and Equipments (2016) and ASHRAE Standard 55-2013: Thermal Environmental Conditions for Human Occupancy. Simulation with ANSYS Fluent is done to prove that the radiant panel formulations from ASHRAE is applicable in this context, and to get more precise parameters specific to this project. Then, simple simulation is done with EnergyPlus (with OpenStudio as its graphical user interface) to determine the thermal comfort of radiant panel system. Based on the design and simulation process, it is shown that the design formulations from ASHRAE can be a good reference (with error of 7,45%) and radiant panels can satisfy ASHRAE’s thermal comfort standard. Compared to split unit AC, an energy saving of 33,09% can be achieved, however it needs a chiller with high COP (to break even with split unit AC’s power consumption, a chiller with COP of higher than 3,486 is needed). The chiller should be located near the panels, and insulation for the chilled water pipe between the chiller and the panels to minimize heat loss to environment.